An acrylonitrile catalyst, a preparation method and application thereof
Patent Information
- Application Number
- CN202310776464.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-06-28
AI Technical Summary
[0003]实际应用中发现,在流化床反应器中长期运行后,尤其是高负荷运行条件下,催化剂与原料的接触时间很短,无法实现催化剂与原料的充分接触,从而导致催化剂活性受到限制,稳定性也不佳,因此目前该领域的催化剂一个重点研究方向就是开发出能够在高负荷下稳定运行的新型丙烯氨氧化制丙烯腈的催化剂
[0032]本发明的丙烯腈催化剂,具有特定的双峰介孔结构,发明人研究发现,本申请特定的孔分布,其中5~8nm的小尺寸介孔有利于催化剂比表面积的提升,促进原料与催化剂的充分接触与反应,18~25nm的大尺寸介孔有利于产物及时从催化剂表面脱附,减少深度氧化,提升反应产物丙烯腈的选择性,从而能保证在更高的反应负荷,即更短的接触时间下反应的稳定进行。
Smart Images

Figure CN119236959B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalysts, and particularly relates to a high-load catalyst for the ammoxidation of propylene to acrylonitrile, its preparation method, and its application. Background Technology
[0002] Acrylonitrile (AN) is a very important organic chemical raw material, used in the synthesis of acrylic fibers, and is also a raw material for acrylonitrile-butadiene-styrene (ABS), styrene-acrylonitrile (SAN), nitrile rubber, adiponitrile, acrylamide, and other derivatives. Currently, the production of acrylonitrile via propylene ammoxidation is the mainstream technology for acrylonitrile production.
[0003] In practical applications, it has been found that after long-term operation in fluidized bed reactors, especially under high-load conditions, the contact time between the catalyst and the feedstock is very short, which makes it impossible to achieve sufficient contact between the catalyst and the feedstock. As a result, the catalyst activity is limited and the stability is also poor. Therefore, a key research direction in this field is to develop new catalysts for the ammoxidation of propylene to acrylonitrile that can operate stably under high loads.
[0004] CN1081488C describes a catalyst for the ammoxidation of propylene to acrylonitrile prepared by introducing elements such as Na, Sr, and Mg. This catalyst is characterized by its ability to operate under high pressure and high load conditions while maintaining a high acrylonitrile yield, and can be used in industrial production. CN109772356A discloses a catalyst for the ammoxidation of propylene to acrylonitrile, which can simultaneously meet the requirements of (1) high catalyst load in industrial expansion units and (2) reduce the generation of carbonyl compounds acrolein and acrylic acid, thereby improving the unit's operating cycle. CN106955717A discloses a high-efficiency, wear-resistant acrylonitrile catalyst prepared by calcining and molding inorganic non-metals such as activated clay, sodium-based montmorillonite, or calcium-based montmorillonite with a silica support.
[0005] Therefore, current methods for increasing the operating load of acrylonitrile catalysts mostly focus on altering their composition, such as increasing the types of metal elements or adjusting the support composition. Currently, the operating load (WWH) of industrial acrylonitrile catalysts during reaction is typically 0.060–0.085 h⁻¹. -1 This means that a unit mass of catalyst can convert 0.06 to 0.085 units of propylene per hour, and under these conditions, the contact time between the catalyst and the feedstock can typically reach 10 seconds. If the load is increased to a higher level, such as 0.12 hours... -1 The contact time will be further shortened to only about 5 seconds. How to make the catalyst still have high conversion rate and selectivity under high load is a difficult problem that needs to be solved in this field. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides an acrylonitrile catalyst, its preparation method, and its application. The acrylonitrile catalyst of this invention can still maintain high conversion rate and selectivity under high load operating conditions.
[0007] The first aspect of the present invention provides an acrylonitrile catalyst comprising an active metal component and a support, wherein the catalyst has a bimodal mesoporous structure, wherein pores with a diameter of 2 to 12 nm occupy 35% to 55% of the total pore volume, and the most probable pore size is located at 5 to 8 nm; pores >12 nm and ≤35 nm occupy 45% to 65% of the total pore volume, and the most probable pore size is located at 18 to 25 nm.
[0008] Furthermore, the active metal component includes one or more of Mo, Bi, Fe, Ni, and Mg, preferably including all of Mo, Bi, Fe, Ni, and Mg. The support includes a silica-alumina based support and / or a silica / alumina mixture.
[0009] Furthermore, the catalyst has a small pore size of 5-8 nm, which is generated by the close packing of the active metal oxide itself, and a large pore size of 18-25 nm, which is generated by the hard template of the polymer resin.
[0010] Furthermore, the polymer resin includes at least one of phenolic resin, urea-formaldehyde resin, or melamine resin, preferably urea-formaldehyde resin.
[0011] Furthermore, based on the weight of the catalyst, the total content of the active metal component, calculated as oxides, is 45% to 60%, and the content of the support is 40% to 55%.
[0012] Furthermore, the catalyst has a specific surface area of 45–80 m². 2 / g.
[0013] The second aspect of the present invention provides a method for preparing an acrylonitrile catalyst, comprising: dissolving and mixing an active component and a support, further compounding the mixture with a polymer resin to obtain a mixed slurry, and obtaining the catalyst by drying and calcination.
[0014] Furthermore, the preparation method of the acrylonitrile catalyst specifically includes:
[0015] (1) The active component precursor containing Mo is heated and dissolved, and then mixed with the support;
[0016] (2) The precursor solution containing at least one active metal component from Bi, Fe, Ni and Mg is mixed with the material obtained in step (1) to obtain a mixed slurry;
[0017] (3) The polymer monomer is heated and dissolved in water and added to the mixed slurry in step (2). Then formaldehyde monomer solution and alkaline solution are added, and the mixture is stirred to obtain the final slurry. Then it is dried and calcined to obtain acrylonitrile catalyst.
[0018] Furthermore, the precursor containing the active metal element is a water-soluble salt containing the active metal element, wherein the active component precursor containing Mo is preferably a Mo-containing oxyacid ammonium salt, preferably (NH4)6Mo7O 24 Or its hydrate. The precursor solution containing at least one active metal component of Bi, Fe, Ni, and Mg is one or more of halides, alkoxides, nitrates, or acetates, preferably nitrates, such as bismuth nitrate, ferric nitrate, nickel nitrate, magnesium nitrate, etc.
[0019] Furthermore, in this invention, the heating and dissolving process can be carried out at conventional temperatures in the art, as long as sufficient dissolution and mixing are achieved.
[0020] Further, in step (1), the carrier is selected from silica sol, solid silica or silica / alumina molecular sieve carrier, preferably silica sol.
[0021] Further, in step (3), the polymer monomer is selected from at least one of urea, phenol, resorcinol, and melamine, preferably urea and / or phenol, and more preferably urea.
[0022] Further, in step (3), the total amount of formaldehyde monomer and polymer monomer added is 5% to 20% of the total mass of the active metal precursor, preferably 8% to 15%.
[0023] Further, in step (3), the mass concentration of the formaldehyde monomer solution is 20% to 50%, preferably 25% to 40%. The molar ratio of the amount of formaldehyde monomer added to the polymer monomer is preferably 0.8:1 to 1.5:1.
[0024] Further, in step (3), the alkaline solution is selected from at least one of ammonia solution, sodium hydroxide solution, and potassium hydroxide solution, preferably ammonia solution. The mass concentration of the alkaline solution is preferably 10% to 15%, and the mass ratio of the amount of alkaline solution added to the formaldehyde monomer solution is preferably 0.1:1 to 0.5:1.
[0025] Further, in step (3), the stirring conditions include: time 15-30 min, temperature 80-120℃, and stirring speed 150-350 rpm.
[0026] Further, in step (3), the drying conditions include: a drying temperature of 200–480°C, preferably 300–400°C, and a drying time of 0.5–4 h, preferably 0.5–1.5 h. The drying method is spray drying, the heat source is air, and the average diameter of the spray droplets is 40–200 μm, preferably 40–180 μm.
[0027] Further, in step (3), the calcination conditions include: a calcination temperature of 200–700°C, preferably 400–650°C, and a calcination time of 3–8 hours, preferably 4–6 hours. The calcination is carried out in an oxygen-containing atmosphere, such as in an air atmosphere.
[0028] A third aspect of the present invention provides the application of the above-described acrylonitrile catalyst or the acrylonitrile catalyst prepared by the above method in the preparation of acrylonitrile.
[0029] The specific application is as follows: in the presence of the acrylonitrile catalyst, propylene undergoes an ammonia oxidation reaction to produce acrylonitrile in the presence of ammonia and oxygen.
[0030] Specific reaction conditions include: a molar ratio of propylene / ammonia / air (based on oxygen content) of 1:1.2–1.3:9.6–10.0; a reaction temperature of 420–435℃; a reaction pressure (gauge pressure) of 0.06–0.14 MPa; and a catalyst loading of 0.08–0.12 h⁻¹. -1 Preferably, it is 0.09–0.12 h. -1 .
[0031] Compared with the prior art, the advantages of the present invention are as follows:
[0032] The acrylonitrile catalyst of the present invention has a specific bimodal mesoporous structure. The inventors have discovered that the specific pore distribution of this application, wherein the small-sized mesopores of 5-8 nm are beneficial to increasing the specific surface area of the catalyst, promoting full contact and reaction between the raw materials and the catalyst, and the large-sized mesopores of 18-25 nm are beneficial to the timely desorption of products from the catalyst surface, reducing deep oxidation and improving the selectivity of the reaction product acrylonitrile, thereby ensuring the stable progress of the reaction under higher reaction load, i.e. shorter contact time.
[0033] In the acrylonitrile catalyst preparation method of the present invention, two types of mesopores with different sizes are formed by polymer-induced assembly and metal oxide self-close packing, respectively. Compared with other pore-forming agents, the mesopore distribution of the catalyst in this application is more concentrated without affecting the overall catalytic performance of the catalyst. The resulting acrylonitrile catalyst can withstand high reaction loads (e.g., 0.12 h⁻¹). -1 It can maintain a high acrylonitrile single-pass yield for a long time, and can still maintain a high propylene conversion rate and acrylonitrile single-pass yield after long-term operation. Attached Figure Description
[0034] Figure 1 This is a pore size distribution diagram of the acrylonitrile catalyst prepared in Example 1;
[0035] Figure 2 The pore size distribution diagram is shown for the acrylonitrile catalyst prepared in Comparative Example 1.
[0036] Figure 3 The image shows the pore size distribution of the acrylonitrile catalyst prepared in Comparative Example 2. Detailed Implementation
[0037] To more clearly illustrate the present invention, the following description, in conjunction with embodiments and accompanying drawings, further clarifies the invention. Those skilled in the art should understand that the specific descriptions below are illustrative rather than restrictive and should not be construed as limiting the scope of protection of the present invention.
[0038] In this invention, the specific surface area and pore size are measured using a Tristar physical adsorption instrument. Before testing, the samples undergo heating and vacuum degassing. Porosity was measured at 77 K, and the specific surface area was calculated using the Brunauer-Emmett-Teller (BET) method. The pore size distribution and pore volume can be calculated from the isothermal adsorption branch using the Barrettner-Joyner-Halenda (BJH) model.
[0039] In this invention, gas chromatography is used for online analysis of the product gas. The conversion rate of propylene, the selectivity of acrylonitrile, and the single-pass yield are used as indicators to evaluate the catalyst performance. The definitions of these two parameters are as follows:
[0040] Acrylonitrile conversion rate (%) = (moles of propylene reacted / moles of propylene fed) × 100%
[0041] Acrylonitrile selectivity (%) = (moles of acrylonitrile produced / moles of propylene reacted) × 100%
[0042] Acrylonitrile single-pass yield (%) = (moles of acrylonitrile produced / moles of propylene fed) × 100%
[0043]
Example 1
[0044] (1) 93.7 grams of (NH4)6Mo7O 24 • Dissolve 4H2O in water by heating, and add 350 grams of silica sol with a mass fraction of 30% to obtain material I;
[0045] (2) Dissolve 9.6 g Bi(NO3)3·5H2O, 49.7 g Ni(NO3)2·6H2O, 30.2 g Fe(NO3)3·9H2O, and 16.2 g Mg(NO3)2·6H2O in water and add them to material I to obtain mixed slurry II;
[0046] (3) Weigh 14.0 g of urea, dissolve it in water, and add it to mixed slurry II. Then add 25.0 g of formaldehyde solution with a mass concentration of 28% and 5.0 g of ammonia solution with a mass concentration of 14%. Stir at 300 rpm for 0.5 hours at 100°C to obtain a slurry. Spray dry the slurry at 350°C for 0.5 hours to obtain particulate matter. Calcinate the particulate matter in air at 600°C for 3 hours to obtain acrylonitrile catalyst A, whose general formula is:
[0047] 50% Mo 12.00 Bi 0.43 Fe 1.63 Ni 3.72 Mg 1.38 O 44.18 +50% SiO2
[0048] The specific surface area of acrylonitrile catalyst A is 69.3 m². 2 / g, with a bimodal mesoporous structure, see details. Figure 1 Among them, pores with a diameter of 2 to 12 nm account for 45% of the total pore volume, with the most probable pore size at 6.0 nm; pores with a diameter greater than 12 nm and less than or equal to 35 nm account for 54% of the total pore volume, with the most probable pore size at 21 nm.
[0049] The reaction conditions for the ammoxidation of propylene to acrylonitrile using the above catalyst are as follows: In a millimeter-scale fluidized bed reactor, the reaction conditions were: reaction temperature: 420℃; reaction pressure: 0.085 MPa; catalyst loading: 300 g; catalyst propylene loading (WWH): 0.12 h. -1 Raw material ratio (molar): C3 = / NH3 / air = 1 / 1.25 / 9.7. After 3 hours of operation, the propylene conversion rate was 98.26%, the acrylonitrile selectivity was 83.81%, and the acrylonitrile single-pass yield was 82.35%. After 500 hours of operation, the propylene conversion rate was 97.95%, the acrylonitrile selectivity was 83.57%, and the acrylonitrile single-pass yield was 81.86%.
[0050]
Example 2
[0051] (1) 93.7 grams of (NH4)6Mo7O 24• Dissolve 4H2O in water by heating, and add 350 grams of silica sol with a mass fraction of 30% to obtain material I;
[0052] (2) Dissolve 9.6 g Bi(NO3)3·5H2O, 49.7 g Ni(NO3)2·6H2O, 30.2 g Fe(NO3)3·9H2O, and 16.2 g Mg(NO3)2·6H2O in water and add them to material I to obtain mixed slurry II;
[0053] (3) Weigh 22.0 g of resorcinol, dissolve it in water, and add it to mixed slurry II. Then, add 25.0 g of formaldehyde solution with a mass concentration of 28% and 5.0 g of ammonia solution with a mass concentration of 14% in sequence. Stir at 300 rpm for 0.5 hours at 100°C to obtain a slurry. Spray dry the slurry at 350°C for 0.5 hours to obtain particulate matter. Calcine the particulate matter in air at 600°C for 3 hours to obtain acrylonitrile catalyst B.
[0054] Acrylonitrile catalyst B has a specific surface area of 68.4 m². 2 / g has a bimodal mesoporous structure, in which pores with a diameter of 2 to 12 nm account for 44% of the total pore volume, with the most probable pore size at 6.5 nm; pores with a diameter greater than 12 nm and less than or equal to 35 nm account for 55% of the total pore volume, with the most probable pore size at 22.3 nm.
[0055] The reaction conditions for the ammoxidation of propylene to acrylonitrile using the above catalyst are as follows: In a millimeter-scale fluidized bed reactor, the reaction conditions were: reaction temperature: 420℃; reaction pressure: 0.085 MPa; catalyst loading: 300 g; catalyst propylene loading (WWH): 0.12 h. -1 Raw material ratio (molar): C3 = / NH3 / air = 1 / 1.25 / 9.7. After 3 hours of operation, the propylene conversion rate was 98.19%, the acrylonitrile selectivity was 83.76%, and the acrylonitrile single-pass yield was 82.24%. After 500 hours of operation, the propylene conversion rate was 97.78%, the acrylonitrile selectivity was 83.50%, and the acrylonitrile single-pass yield was 81.65%.
[0056]
Example 3
[0057] (1) 103.1 g of (NH4)6Mo7O 24 • Dissolve 4H2O in water by heating, add 105g of 600-mesh ZSM-5 molecular sieve and stir evenly to obtain material I;
[0058] (2) Dissolve 10.6 g Bi(NO3)3·5H2O, 54.7 g Ni(NO3)2·6H2O, 33.2 g Fe(NO3)3·9H2O, and 17.6 g Mg(NO3)2·6H2O in water and add them to material I to obtain mixed slurry II;
[0059] (3) Weigh 15.4 g of urea, dissolve it in water, and add it to mixed slurry II. Then, add 25.0 g of formaldehyde solution with a mass concentration of 28% and 7.0 g of ammonia solution with a mass concentration of 10% in sequence. Stir at 300 rpm for 0.5 hours at 100°C to obtain a slurry. Spray dry the slurry at 350°C for 0.5 hours to obtain particulate matter. Calcine the particulate matter in air at 600°C for 3 hours to obtain acrylonitrile catalyst C.
[0060] The specific surface area of acrylonitrile catalyst C reaches 72.3 m². 2 / g has a bimodal mesoporous structure, in which pores with a diameter of 2 to 12 nm account for 48% of the total pore volume, with the most probable pore size at 7.1 nm; pores with a diameter greater than 12 nm and less than or equal to 35 nm account for 50% of the total pore volume, with the most probable pore size at 24.0 nm.
[0061] The reaction conditions for the ammoxidation of propylene to acrylonitrile using the above catalyst are as follows: In a millimeter-scale fluidized bed reactor, the reaction conditions were: reaction temperature: 420℃; reaction pressure: 0.085 MPa; catalyst loading: 300 g; catalyst propylene loading (WWH): 0.12 h. -1 Raw material ratio (molar): C3 = / NH3 / air = 1 / 1.25 / 9.7. After 3 hours of operation, the propylene conversion rate was 98.10%, the acrylonitrile selectivity was 83.68%, and the acrylonitrile single-pass yield was 82.09%. After 500 hours of operation, the propylene conversion rate was 97.68%, the acrylonitrile selectivity was 83.37%, and the acrylonitrile single-pass yield was 81.44%.
[0062]
Example 4
[0063] (1) 93.7 grams of (NH4)6Mo7O 24 • Dissolve 4H2O in water by heating, and add 350 grams of silica sol with a mass fraction of 30% to obtain material I;
[0064] (2) Dissolve 9.6 g Bi(NO3)3·5H2O, 49.7 g Ni(NO3)2·6H2O, 30.2 g Fe(NO3)3·9H2O, and 16.2 g Mg(NO3)2·6H2O in water and add them to material I to obtain mixed slurry II;
[0065] (3) Weigh 14.0 g of urea, dissolve it in water, and add it to mixed slurry II. Then, add 25.0 g of formaldehyde solution with a mass concentration of 28% and 14.0 g of sodium hydroxide aqueous solution with a mass concentration of 5% in sequence. Stir at 250 rpm for 0.5 hours at 120°C to obtain a slurry. Spray dry the slurry at 350°C for 0.5 hours to obtain particulate matter. Calcine the particulate matter in air at 620°C for 3 hours to obtain acrylonitrile catalyst D.
[0066] The specific surface area of acrylonitrile catalyst D reaches 65.8 m². 2 / g has a bimodal mesoporous structure, in which pores with a diameter of 2 to 12 nm account for 50% of the total pore volume, with the most probable pore size at 7.2 nm; pores with a diameter greater than 12 nm and less than or equal to 35 nm account for 49% of the total pore volume, with the most probable pore size at 23.5 nm.
[0067] The reaction conditions for the ammoxidation of propylene to acrylonitrile using the above catalyst are as follows: In a millimeter-scale fluidized bed reactor, the reaction conditions were: reaction temperature: 420℃; reaction pressure: 0.085 MPa; catalyst loading: 300 g; catalyst propylene loading (WWH): 0.12 h. -1 Raw material ratio (molar): C3 = / NH3 / air = 1 / 1.25 / 9.7. After 3 hours of operation, the propylene conversion rate was 98.18%, the acrylonitrile selectivity was 83.78%, and the acrylonitrile single-pass yield was 82.26%. After 500 hours of operation, the propylene conversion rate was 97.76%, the acrylonitrile selectivity was 83.48%, and the acrylonitrile single-pass yield was 81.61%.
[0068]
Example 5
[0069] (1) 93.7 grams of (NH4)6Mo7O 24 • Dissolve 4H2O in water by heating, and add 350 grams of silica sol with a mass fraction of 30% to obtain material I;
[0070] (2) Dissolve 9.6 g Bi(NO3)3·5H2O, 49.7 g Ni(NO3)2·6H2O, 30.2 g Fe(NO3)3·9H2O, and 16.2 g Mg(NO3)2·6H2O in water and add them to material I to obtain mixed slurry II;
[0071] (3) Weigh 25.2 g of urea, dissolve it in water, and add it to mixed slurry II. Then, add 45 g of formaldehyde solution with a mass concentration of 28% and 9.0 g of ammonia solution with a mass concentration of 14% in sequence. Stir at 300 rpm for 0.5 hours at 100°C to obtain a slurry. Spray dry the slurry at 350°C for 0.5 hours to obtain particulate matter. Calcine the particulate matter in air at 600°C for 3 hours to obtain acrylonitrile catalyst E.
[0072] Acrylonitrile catalyst E has a specific surface area of 60.5 m². 2 / g has a bimodal mesoporous structure, in which pores with a diameter of 2 to 12 nm account for 47% of the total pore volume, with the most probable pore size at 7.9 nm; pores with a diameter >12 nm and ≤35 nm account for 51% of the total pore volume, with the most probable pore size at 24.5 nm.
[0073] The reaction conditions for the ammoxidation of propylene to acrylonitrile using the above catalyst are as follows: In a millimeter-scale fluidized bed reactor, the reaction conditions were: reaction temperature: 420℃; reaction pressure: 0.085 MPa; catalyst loading: 300 g; catalyst propylene loading (WWH): 0.12 h. -1 Raw material ratio (molar): C3 = / NH3 / air = 1 / 1.25 / 9.7. After 3 hours of operation, the propylene conversion rate was 98.08%, the acrylonitrile selectivity was 83.65%, and the acrylonitrile single-pass yield was 82.04%. After 500 hours of operation, the propylene conversion rate was 97.67%, the acrylonitrile selectivity was 83.25%, and the acrylonitrile single-pass yield was 81.31%.
[0074] Comparative Example 1
[0075] (1) 93.7 grams of (NH4)6Mo7O 24 • Dissolve 4H2O in water by heating, and add 350 grams of silica sol with a mass fraction of 30% to obtain material I;
[0076] (2) Dissolve 9.6 g Bi(NO3)3·5H2O, 49.7 g Ni(NO3)2·6H2O, 30.2 g Fe(NO3)3·9H2O, and 16.2 g Mg(NO3)2·6H2O in water and add the solution to material I. Stir at 300 rpm for 0.5 hours at 100°C to obtain mixed slurry II. Spray dry the slurry at 350°C for 0.5 hours to obtain granules. Calcine the granules in air at 600°C for 3 hours to obtain acrylonitrile catalyst F.
[0077] The specific surface area of acrylonitrile catalyst F is 37.0 m². 2 / g, does not have a bimodal mesoporous structure, and the most probable pore size is 9.1nm. See details. Figure 2 .
[0078] The reaction conditions for the ammoxidation of propylene to acrylonitrile using the above catalyst are as follows: In a millimeter-scale fluidized bed reactor, the reaction conditions were: reaction temperature: 420℃; reaction pressure: 0.085 MPa; catalyst loading: 300 g; catalyst propylene loading (WWH): 0.12 h. -1 Raw material ratio (molar): C3 = / NH3 / air = 1 / 1.25 / 9.7. After 3 hours of operation, the propylene conversion rate was 95.24%, the acrylonitrile selectivity was 81.27%, and the acrylonitrile single-pass yield was 77.40%. After 500 hours of operation, the propylene conversion rate was 93.06%, the acrylonitrile selectivity was 78.05%, and the acrylonitrile single-pass yield was 72.63%.
[0079] Comparative Example 2
[0080] (1) 93.7 grams of (NH4)6Mo7O 24 • Dissolve 4H2O in water by heating, and add 350 grams of silica sol with a mass fraction of 30% to obtain material I;
[0081] (2) Dissolve 9.6 g Bi(NO3)3·5H2O, 49.7 g Ni(NO3)2·6H2O, 30.2 g Fe(NO3)3·9H2O, and 16.2 g Mg(NO3)2·6H2O in water and add them to material I to obtain mixed slurry II;
[0082] (3) Weigh 35.0 g of urea, dissolve it in water, and add it to mixed slurry II. Then, add 62.5 g of formaldehyde solution with a mass concentration of 28% and 12.5 g of ammonia solution with a mass concentration of 14% in sequence. Stir at 300 rpm for 0.5 hours at 100°C to obtain a slurry. Spray dry the slurry at 350°C for 0.5 hours to obtain particulate matter. Calcine the particulate matter in air at 600°C for 3 hours to obtain acrylonitrile catalyst G.
[0083] The specific surface area of acrylonitrile catalyst G is 42.6 m². 2 / g, exhibiting a bimodal mesoporous structure, but with most probable pore sizes located at 13.1 nm and 35.4 nm, see details. Figure 3 .
[0084] The reaction conditions for the ammoxidation of propylene to acrylonitrile using the above catalyst are as follows: In a millimeter-scale fluidized bed reactor, the reaction conditions were: reaction temperature: 420℃; reaction pressure: 0.085 MPa; catalyst loading: 300 g; catalyst propylene loading (WWH): 0.12 h. -1 Raw material ratio (molar): C3 = / NH3 / air = 1 / 1.25 / 9.7. After 3 hours of operation, the propylene conversion rate was 93.65%, the acrylonitrile selectivity was 79.86%, and the acrylonitrile single-pass yield was 74.79%. After 500 hours of operation, the propylene conversion rate was 91.14%, the acrylonitrile selectivity was 75.9%, and the acrylonitrile single-pass yield was 69.18%.
[0085] Table 1 Comparison of catalyst parameters in the comparative examples.
[0086]
[0087] The specific embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combining the various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. An acrylonitrile catalyst, comprising an active metal component and a support, characterized in that, The catalyst has a bimodal mesoporous structure, wherein pores with a diameter of 2-12 nm account for 35%-55% of the total pore volume, and the most probable pore size is located at 5-8 nm; pores with a diameter >12 nm and ≤35 nm account for 45%-65% of the total pore volume, and the most probable pore size is located at 18-25 nm. The catalyst was prepared using the following method: (1) The precursor containing the active component containing Mo is dissolved by heating and then mixed with the support; (2) The precursor solution containing at least one active metal component from Bi, Fe, Ni and Mg is mixed with the material obtained in step (1) to obtain a mixed slurry; (3) The polymer monomer is heated and dissolved in water and added to the mixed slurry in step (2). Then formaldehyde monomer solution and alkaline solution are added, and the mixture is stirred to obtain the final slurry. Then it is dried and calcined to obtain acrylonitrile catalyst.
2. The catalyst according to claim 1, characterized in that, The carrier includes a silica-alumina based carrier and / or a silica / alumina mixture.
3. The catalyst according to claim 1, characterized in that, The active metal components include Mo, Bi, Fe, Ni, and Mg.
4. The catalyst according to claim 1, characterized in that, The total content of the active metal component, calculated as oxide, is 45% to 60% by weight of the catalyst, and the content of the support is 40% to 55%.
5. The method for preparing the catalyst according to any one of claims 1-4, characterized in that, include: (1) The precursor containing the active component containing Mo is dissolved by heating and then mixed with the support; (2) The precursor solution containing at least one active metal component from Bi, Fe, Ni and Mg is mixed with the material obtained in step (1) to obtain a mixed slurry; (3) The polymer monomer is heated and dissolved in water and added to the mixed slurry in step (2). Then formaldehyde monomer solution and alkaline solution are added, and the mixture is stirred to obtain the final slurry. Then it is dried and calcined to obtain acrylonitrile catalyst.
6. The method according to claim 5, characterized in that, In step (3), the polymer monomer is selected from at least one of urea, phenol, resorcinol, and melamine; and / or, In step (3), the total amount of formaldehyde monomer and polymer monomer added is 5% to 20% of the total mass of the active metal precursor.
7. The method according to claim 6, characterized in that, In step (3), the polymer monomer is selected from urea and / or phenol.
8. The method according to claim 6, characterized in that, In step (3), the polymer monomer is selected from urea.
9. The method according to claim 6, characterized in that, In step (3), the total amount of formaldehyde monomer and polymer monomer added is 8% to 15% of the total mass of the active metal precursor.
10. The method according to claim 5, characterized in that, In step (3), the mass concentration of the formaldehyde monomer solution is 20%~50%; the molar ratio of the amount of formaldehyde monomer added to the polymer monomer is 0.8:1~1.5:
1.
11. The method according to claim 10, characterized in that, In step (3), the mass concentration of the formaldehyde monomer solution is 25%~40%.
12. The method according to claim 5, characterized in that, In step (3), the alkaline solution is selected from at least one of ammonia solution, sodium hydroxide solution and potassium hydroxide solution.
13. The method according to claim 12, characterized in that, The mass concentration of the alkaline solution is 10% to 15%; the mass ratio of the amount of alkaline solution added to the mass of the formaldehyde monomer solution is 0.1:1 to 0.5:
1.
14. The method according to claim 5, characterized in that, In step (3), the polymer resin obtained from the polymer monomer and the formaldehyde monomer includes at least one of phenolic resin, urea-formaldehyde resin or melamine resin.
15. The method according to claim 5, characterized in that, In step (3), the drying conditions include: a drying temperature of 200~480℃ and a drying time of 0.5~4h; and / or, the calcination conditions include: a calcination temperature of 200~700℃ and a calcination time of 3~8h.
16. The method according to claim 15, characterized in that, In step (3), the drying conditions include: a drying temperature of 300~400℃ and a drying time of 0.5~1.5h; and / or, the calcination conditions include: a calcination temperature of 400~650℃ and a calcination time of 4~6h.
17. The use of the catalyst according to any one of claims 1-4 or the catalyst prepared by the method according to any one of claims 5-16 in the preparation of acrylonitrile.
Citation Information
Patent Citations
Preparation method for efficient and wear-resisting acrylonitrile catalyst
CN106955717A
Catalyst for ammonoxidating propylene to produce acrylonitrile
CN1081488C
Acrylonitrile catalyst and preparation method and application thereof
CN109772356A
Acrylonitrile catalyst
CN107398288A
Catalyst for propane dehydrogenation and preparation method thereof, and method for preparing propylene from propane through dehydrogenation
CN109384639A
